War, Peace and Stabilisation: Critically Reconceptualising Stability in Southern Afghanistan. Issue 1 (11th June 2013) - Robert Carter, William
This article critically treats stabilisation theory and programming through a perspective of peace and conflict, and argues for stabilisation's reconceptualisation. Through tracking the concept's emergence, it outlines that stabilisation is theoretically rooted in an insecurity-underdevelopment problematic and relies on the Liberal Peace thesis as a solution. When this concept was operationalised in southern Afghanistan, however, it was translated into a praxis informed by state-building and counterinsurgency imperatives. This approach ultimately produced confused, sometimes counterproductive, effects: simultaneously engendering a liberal, negative, rented and victor's peace. The article concludes by arguing that stabilisation should be reconceptualised so that it pursues a positive and hybrid peace if it is to be a more effective source of guidance for policy and practice. The first step is to denaturalise the 'formal' state in conflict and fragile environments as being seen as a panacea to all ills of instability.